Reduced Acquisition Time [18F]GE-180 PET Scanning Protocol Replaces Gold-Standard Dynamic Acquisition in a Mouse Ischemic Stroke Model - Zatcepin, Artem; Heindl, Steffanie; Schillinger, Ulrike; Kaiser, Lena; Lindner, Simon; Bartenstein, Peter; Kopczak, Anna; Liesz, Arthur; Brendel, Matthias; Ziegler, Sibylle I. (Frontiers in Medicine, 2022)
Aim Understanding neuroinflammation after acute ischemic stroke is a crucial step on the way to an individualized post-stroke treatment. Microglia activation, an essential part of neuroinflammation, can be assessed using [18F]GE-180 18 kDa translocator protein positron emission tomography (TSPO-PET). However, the commonly used 60-90 min post-injection (p.i.) time window was not yet proven to be suitable for post-stroke neuroinflammation assessment. In this study, we compare semi-quantitative estimates derived from late time frames to quantitative estimates calculated using a full 0-90 min dynamic scan in a mouse photothrombotic stroke (PT) model. Materials and Methods Six mice after PT and six sham mice were included in the study. For a half of the mice, we acquired four serial 0-90 min scans per mouse (analysis cohort) and calculated standardized uptake value ratios (SUVRs; cerebellar reference) for the PT volume of interest (VOI) in five late 10 min time frames as well as distribution volume ratios (DVRs) for the same VOI. We compared late static 10 min SUVRs and the 60-90 min time frame of the analysis cohort to the corresponding DVRs by linear fitting. The other half of the animals received a static 60-90 min scan and was used as a validation cohort. We extrapolated DVRs by using the static 60-90 min p.i. time window, which were compared to the DVRs of the analysis cohort. Results We found high linear correlations between SUVRs and DVRs in the analysis cohort for all studied 10 min time frames, while the fits of the 60-70, 70-80, and 80-90 min p.i. time frames were the ones closest to the line of identity. For the 60-90 min time window, we observed an excellent linear correlation between SUVR and DVR regardless of the phenotype (PT versus sham). The extrapolated DVRs of the validation cohort were not significantly different from the DVRs of the analysis group. Conclusion Simplified quantification by a reference tissue ratio of the late 60-90 min p.i. [18F]GE-180 PET image can replace full quantification of a dynamic scan for assessment of microglial activation in the mouse PT model.